Requirements for Applying Decision Support Systems in Palestinian Higher Education Institutions - Applied Study on Al - Aqsa University in Gaza - Mazen J. Al Shobaki; Samy S. Abu Naser (International Journal of Information Technology and Electrical Engineering, 2017)
The purpose of this research is to explain the requirements of applying decision support systems in Palestinian higher education institutions- an applied study on Al-Aqsa University in Gaza. The researchers used the descriptive and analytical methods. The study population is the staff members of Al-Aqsa University in Gaza. The researchers used the random sample method. 150 questionnaires were distributed to the study population and 126 responses were obtained back with a recovery rate (84%). The results of the study showed the followings: There was an approval by the sample members of the requirements of the application of decision support systems in general. The approval of "Support of senior management for the use of decision support systems" reached (62.60%). While the level of approval for "the possibilities for using decision support systems" (69.03%). Finally, the level of approval for the type of decision support systems used was 69.73%. The results showed that there were no statistically significant differences between the responses of respondents on the requirements of applying decision support systems due to the demographic variables (gender, age, qualification, and years of service). The study also concluded with a number of recommendations, the most important of which are the need to keep abreast of developments in the field of business, including the adoption of modern organizations on decision support systems, which represent the true value of organizations. It is a good for the university to rely entirely on decision support systems because it provides the management with the good information that the university needs. It is good for the university to increase attention and rely on modern systems because it works to develop performance and achieve the objectives of planning
Keywords: 330; Decision Support Systems; Palestinian Higher Education Institutions; Palestinian Universities; Al-Aqsa University; Gaza Strip